2019
DOI: 10.15295/bmij.v7i5.1382
|View full text |Cite
|
Sign up to set email alerts
|

Toplumsal Ci̇nsi̇yet Eşi̇tsi̇zli̇ği̇ Ve Ai̇le İçi̇ Şi̇ddet Etki̇leşi̇mi̇: Üni̇versi̇te Öğrenci̇leri̇ Üzeri̇ne Ni̇tel Bi̇r Araştirma

Abstract: Toplumsal cinsiyete bağlı eşitsizlikler gelişmekte olan ülkelerde daha çok görülmektedir. Bu noktadan hareketle araştırmada, toplumsal cinsiyet eşitsizliği algısı ve toplumsal cinsiyet eşitsizliğinin de aile içi şiddet ile ilişkisine dair görüşler üniversite öğrencileri örnekleminde nitel bir araştırmayla ortaya konulmaya çalışılmıştır. Bu araştırma, birincil verileri elde etmek için nitel bir araştırma yöntemi olan olgubilim (fenomenoloji) deseninde tasarlanmıştır. Araştırmada rastgele amaçlı örneklem yöntemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…This difference may be because men typically avoid reporting negligence, and that women express their feelings and experiences more easily than men. Today, as a result of patriarchal family structures, gender inequality is an ongoing problem that affects all areas of life (Aslan & Demirci, 2019). Studies have shown that women face more pressure in their childhood and are sometimes unable to continue their education (Aslan & Demirci, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be because men typically avoid reporting negligence, and that women express their feelings and experiences more easily than men. Today, as a result of patriarchal family structures, gender inequality is an ongoing problem that affects all areas of life (Aslan & Demirci, 2019). Studies have shown that women face more pressure in their childhood and are sometimes unable to continue their education (Aslan & Demirci, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Today, as a result of patriarchal family structures, gender inequality is an ongoing problem that affects all areas of life (Aslan & Demirci, 2019). Studies have shown that women face more pressure in their childhood and are sometimes unable to continue their education (Aslan & Demirci, 2019). The oppressive upbringing of women and the deprivation of education lead them to engage in similar behaviours when they become mothers, thus perpetuating the cycle of trauma in their children.…”
Section: Discussionmentioning
confidence: 99%
“…Bu çalışmada katılımcıların en fazla psikolojik şiddete (%21.2) maruz kaldığı bulunmuştur. Literatürde de bu araştırma sonucuna paralel olarak bazı çalışmalarda en fazla maruz kalınan şiddet türünün psikolojik şiddet olduğu belirlenmiştir (4,29). Türkiye'de kadınların yaşamlarının herhangi bir döneminde maruz kaldıkları duygusal şiddet oranı %44, son 12 ayda ise %26 olarak bildirilmiştir (7).…”
Section: üNiversite öğRencilerinin öRnek Olaydaki şIddet Uygulayan Bi...unclassified
“…7 Gender equality does not mean that females and males will be the same. However, it means that the rights, responsibilities, and opportunities of females and males will not change depending on whether they are born as male or female 8 . Any exclusion or restriction based on gender that pursues the goal of trying to hinder individuals from enjoying such rights or nullifying leads to social gender inequality.…”
Section: Introductionmentioning
confidence: 99%